On the effect of TiO2 nanocrystallites over the plasmonic photodegradation by Au nanoparticles. (1st October 2018) - Wang, Jiale; Barbosa, Eduardo C.M.; Fang, Zebo; Parussulo, André L.A.; dos Reis, Flavia V.E.; Ando, Rômulo A.; Araki, Koiti; Toma, Henrique E.; Camargo, Pedro H.C.
Abstract: In this paper, we aimed at investigating the effect of the presence of small TiO2 crystallites over the transfer of hot electrons from Au nanoparticles (NPs) mediated by the surface plasmon resonance (SPR) excitation and its subsequent photocatalytic activities. To this end, we employed TiO2 colloidal spheres composed of TiO2 crystallites of 8.5 nm in size decorated with Au NPs (TiO2 –Au) of 17 nm in size over the TiO2 surface as model materials. Moreover, the photocatalytic degradation of methylene blue (MB) under visible light excitation was employed as a target plasmonic transformation. We found that the plasmonic photocatalytic activity was significantly higher for the TiO2 –Au hybrid relative to its individual Au NPs or TiO2 counterparts under excitation at 633 nm. These results could be explained based on the transfer of hot electrons generated upon the SPR excitation from Au NPs to the TiO2 conduction band in the TiO2 –Au material, which will be recombined on the surface of TiO2 crystallites or at the interface between TiO2 crystallites, decreasing electrons density in Au NPs that lead to the formation of hydroxyl radicals that contribute and improve the photocatalytic degradation of MB. This mechanism was supported by the fact that the presence of TiO2 leads to a decrease in the p ‐aminothiophenol to p, p ′‐dimercaptoazobenzene SPR‐mediated oxidation in the TiO2 –Au relative to Au NPs. We believe that the results reported herein suggest that TiO2 –Au materials may represent attractive systems for designing plasmonic photocatalysts with improved performances towards a variety of transformations using solar/visible light as the energy input. Abstract : TiO2 –Au material presented improved plasmonic photocatalytic activity under visible light. TiO2 formed by small crystallites enhances plasmonic photocatalytic performance. This mechanism involving the transfer of SPR‐excited hot electrons from Au to TiO2 was further supported by probing the SPR‐mediated catalytic oxidation of p ‐aminothiophenol (PATP) to p, p ′‐dimercaptoazobenzene (DMAB).